Niels Lyhne - Jacobsen, J. P. (Jens Peter), 1847-1885; Larsen, Hanna Astrup, 1873-1945 (Salt Lake City, UT : Project Gutenberg, 2017)
"Niels Lyhne" by J. P. Jacobsen is a novel written in 1880. This Danish work follows its title character through his renunciation of faith, personal losses, and growing disillusionment. Considered part of the Scandinavian Modern Breakthrough movement, the novel examines individual struggle, artistic ambition, and the helplessness of the individual. It depicts both the failures of atheism and faith, offering a naturalistic portrait of an atheistic bourgeois intellectual confronting life's disappointments and, ultimately, death. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Niels_Lyhne
Release date is 2017-08-19
E-text prepared by Paul Marshall and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Denmark -- Fiction; Danish fiction -- Translations into English